MIXKIP/RAPCAL: A Computational Package for Integrated Simulations of Large-Scale Atomic Kinetics and Radiation Transport in Non-Local Thermodynamic Equilibrium Plasmas (Communications in Computational Physics, 2021)
In many of the plasmas generated in many fields of the high energy density physics, the radiation can significantly alter the material response. A proper microscopic description of these plasmas entails integrated computer codes that self-consistently combines large-scale atomic kinetics and radiation transport. Due to theinherent complexity of this type of codes and its interest in the area of high energy density physics, new developments in this field are welcomed. In this work, we presentMIXKIP/RAPCAL, an integrated computational package to perform 1D and 2D large-scale non-local thermodynamic equilibrium atomic kinetics and radiation transfer coupled simulations for high energy density plasmas. This package includes differentmodules that allow simulations of non-equilibrium plasmas under different degreesof detail and accuracy, depending on the requirements of the situations to analyze.Comparisons with experimental results of homogeneous optically thick plasmas ofgold and xenon are presented in order to check its accuracy. The influence of different approaches of the spatial discretization of the plasma in the radiation dependentatomic kinetics simulations is also analyzed. Finally, this study is also made for a non-homogeneous optically thick aluminum plasma.
Keywords: Radiative transfer equation; large scale plasma kinetics simulations; self-consistent simulations.